Individual progression of carotid intima media thickness as a surrogate for vascular risk (PROG-IMT): Rationale and design of a meta-analysis project - Lorenz, Matthias W.; Bickel, Horst; Bots, Michiel L.; Breteler, Monique M. B.; Catapano, Alberico L.; Desvarieux, Moise; Hedblad, Bo; Iglseder, Bernhard; Johnsen, Stein Harald; Juraska, Michal; Kiechl, Stefan; Mathiesen, Ellisiv B.; et al. (American Heart Journal, 2010)
Carotid intima media thickness (IMT) progression is increasingly used as a surrogate for vascular risk. This use is supported by data from a few clinical trials investigating statins, but established criteria of surrogacy are only partially fulfilled. To provide a valid basis for the use of IMT progression as a study end point, we are performing a 3-step meta-analysis project based on individual participant data. Objectives of the 3 successive stages are to investigate (1) whether IMT progression prospectively predicts myocardial infarction, stroke, or death in population-based samples; (2) whether it does so in prevalent disease cohorts; and (3) whether interventions affecting IMT progression predict a therapeutic effect on clinical end points. Recruitment strategies, inclusion criteria, and estimates of the expected numbers of eligible studies are presented along with a detailed analysis plan. (Am Heart J 2010; 159: 730-736.e2.)